Toward improved engine performance with crumpled nitrogen-doped graphene based water-ethylene glycol coolant - Amiri, A.; Shanbedi, M.; Chew, B.T.; Kazi, S.N.; Solangi, K.H. (Elsevier, 2016)
Crumpled nitrogen-doped graphene nanosheet (CNDG) is considered a promising carbon-based nanosheet due to its high surface area, superior electrical, thermal and mechanical properties. Herein, CNDG is first prepared and tested as an additive for preparing a new engine coolant. The prepared two-dimensional CNDG feature high electrical conductivity, excellent thermal conductivity and heat transfer properties, permitting the CNDG-based water-ethylene glycol coolants to exhibit excellent Mouromtseff number, electrical properties and heat transfer performance for all temperatures and weight concentrations in a car radiator. Further, steady-state forced convective heat transfer experiments have been performed to evaluate the cooling capabilities of the prepared coolants.